Isolation and identification of gastrointestinal microbiota from the short-nosedfruit bat Cynopterus brachyotis brachyotis - Diane Sunira Daniela; Yau Kit Nga; Ee Ley Chuaa; Yogis Arumugama; Jayaraj V.K (2013)
Studies on the microbial ecology of gut microbiota in bats are limited and such information is necessary in determining the ecological significance of these hosts. Short-nosed fruit bats (Cynopterus brachyotisbrachyotis) are good candidates for microbiota studies given their close association with humans in urbanareas. Thus, this study explores the gut microbiota of this species from Peninsular Malaysia by means of biochemical tests and 16S r RNA gene sequences analysis. The estimation of viable bacteria present in the stomach and intestine of C. b. brachyotis ranged from 3.06 × 1010to 1.36 × 1015CFU/ml for stomach fluid and 1.92 × 1010to 6.10 × 1015CFU/ml for intestinal fluid. A total of 34 isolates from the stomachand intestine of seven C. b. brachyotis were retrieved. A total of 16 species of bacteria from eight gen-era (Bacillus, Enterobacter, Enterococcus, Escherichia, Klebsiella, Pantoea, Pseudomonas and Serratia) werei dentified, Enterobacteriaceae being the most prevalent, contributing 12 out of 16 species isolated. Mostisolates from the Family Enterobacteriaceae have been reported as pathogens to humans and wildlife.With the possibility of human wildlife transmission, the findings of this study focus on the importance of bats as reservoirs of potential bacterial pathogens.